"Welcome to OBGYN World!" A novel recruitment event for medical students organized by the Japan Society of Obstetrics and Gynecology. Issue 2 (23rd November 2022) - Miyake, Ryuta; Komatsu, Hiroaki; Ihira, Kei; Hasegawa, Akihiro; Maeda, Yuto; Takemori, Satoshi; Noguchi, Masashi; Dofutsu, Mihoko; Onodera, Yohei; Shinagawa, Manaka; Suemitsu, Tokumasa; Sugita, Yosuke; et al.
Abstract: "Welcome to OBGYN World!" A novel recruitment event for medical students organized by the Japan Society of Obstetrics and Gynecology. Since 2012, the number of doctors in Japan who specialize in obstetrics and gynecology has shown a decreasing trend. To increase the number of doctors majoring in obstetrics and gynecology, the Japanese Trainees in Obstetrics and Gynecology subcommittee developed a new recruitment event called Welcome to OBGYN World! (WOW!); the aim of this event was to focus on lower grades of medical students. The present report describes the content of WOW! and the results of a post‐event questionnaire administered to participating students and tutors. WOW! was held online in order to avoid the risk of Coronavirus Disease 2019 infection for participants. Sixty of the 82 medical schools nationwide (73.2%) participated in this event. Overall, there were 285 participating students, ranging from first to fourth grade in medical school, and 106 tutors were involved to teach material at the event. In the post‐event questionnaire survey, 97.6% (248/254) and 100% of the participants stated they now had a high degree of interest in obstetrics and gynecology and found the specialty attractive, respectively. Furthermore, 93.6% (90/94) of the tutors stated that WOW! had helped recruitment activities in their universities. Based on this outcome, members of the Japanese Trainees of Obstetrics and Gynecology subcommittee will now try to increase the number of doctors specializing in obstetrics and gynecology by holding WOW! annually.